The roots and evolution of nationalism in Indonesia - Lai, Yew Meng; Maureen De Silva, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The emergence of nationalism in Indonesia began at the dawn of the twentieth century, which ultimately led to the birth a new nation-state in 1949. The seeds of national consciousness were sown, and roots of Indonesian nationalism reached its apex during the Revolution (1945-49), manifesting most profoundly in the fight against the oppression of Dutch colonialism. The Revolution was central to the Indonesian republic’s perception of itself and has been influential in fostering nationalism during the post-independence period. This article examines the roots and evolution as well as dynamics and manifestations of Indonesian nationalism, throughout the different phases of Indonesia’s modern history. In doing so, it addresses three salient questions, namely i) how the seeds of national consciousness were sown; ii) what were the underlying factors/dynamics shaping the nature and development of nationalism; and iii) how nationalism and nationhood manifested in a geographically divided, ethno-culturally diverse state like Indonesia, whose citizenry has remained strongly attached to their traditional ethnological and adat communities. Emphasis is given to both state-oriented and popular manifestations of Indonesian nationalism, to highlight the state/elite-centric nature, and populist drive behind its discourses, agenda, and manifestations.